FIRST REPORT OF COCHLODINIUM POLYKRIKOIDES (DINOPHYCEAE), A HARMFUL ALGAL BLOOM (HAB) SPECIES IN THE COASTAL WATERS OF PENINSULAR MALAYSIA - Harun, Siti NorRohaida; Mohammad-Noor, Normawaty; Ahmad, Zuhairi; Kua, Beng Chu; Saad, Shahbudin; Mohamad Hidayat, Nor Salamah; Mukai, Yukinori (Malaysian Journal of Science (MJS), 2015)
Cochlodinium polykrikoides is known as fish killer. In Malaysia this species has been recorded in Kota Kinabalu, Sabah, Borneo Island. To date, C. polykrikoides has not been recorded in Peninsular Malaysia. This study aims to identify the presence of C. polykrikoides in Peninsular Malaysia particularly in Tanjung Piandang, Kuala Kurau and Kuala Gula located in Perak coastal waters and Straits of Tebrau, Johor. Samplings were carried out for three times at each sampling station. Ten litre of water samples were collected for cell enumeration and identification. For identification, plankton samples were identified under light microscope. Nutrients i.e. nitrate, phosphate and ammonia were determined and physico-chemical parameters (pH, temperature, salinity) were also recorded in-situ. Species was identified as C. polykrikoides based on their morphological characteristics. Result showed that C. polykrikoides was presence in high abundance in both Perak coastal waters and Straits of Tebrau at concentration of 2.5 x 103 cells/L and 4.7 x 103 cells/L, respectively. No significant difference was found between cell abundance at these two locations. pH, salinities and temperatures recorded at both locations range between 7.68 – 7.80, 27.23 – 28.03 psu and 29.32 – 30.90 °C, respectively. There was no significant difference in the physico-chemical parameters (p>0.05) between stations. Regression analysis showed no correlations were between cell abundance and physico-chemical parameters and nutrients. The presence of C. polykrikoides in the coastal waters of Peninsular Malaysia indicates that possible mitigation needs to be given attention by the relevant agencies as this species can bring negative impact to aquaculture industry. Keywords: Cochlodinium polykrikoides; fish-cage; Harmful Algal Bloom; Malaysia; Strait of Malacca